ANALISIS PERPUTARAN KAS DAN PERUBAHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR (SEKTOR INDUSTRI MAKANAN DAN MINUMAN) PERIODE 2015 – 2018 - Henrych Napitupulu; Andhika Napitupulu (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2020)
This study aims to determine the analysis of cash turnover and sales changes both partially and simultaneously on profitability. The sample selection is done by purposive sampling method and from 6 companies. The research method used in this study is a quantitative method. Statistical testing which is multiple linear regression and data analysis techniques using the classic assumption test. F test results, obtained an F value of 4.887 with a significant level of 0.018 means that simultaneously simultaneous cash turnover and changes in sales have a significant effect on profitability. The t-test results partially indicate the level of significance obtained from the free variable cash turnover of 0.082> 0.05, this shows that cash turnover has no significant effect on profitability. While the independent variable sales growth of 0.033 <0.05, this shows that sales growth has a significant effect on profitability